2017
DOI: 10.1002/aur.1850
|View full text |Cite
|
Sign up to set email alerts
|

Reading comprehension of ambiguous sentences by school‐age children with autism spectrum disorder

Abstract: Weak central coherence (processing details over gist), poor oral language abilities, poor suppression, semantic interference, and poor comprehension monitoring have all been implicated to affect reading comprehension in individuals with autism spectrum disorder (ASD). This study viewed the contributions of different supporting skills as a collective set of skills necessary for context integration—a multi-component view—to examine individual differences in reading comprehension in school-age children (8–14 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…Reading intervention may also need to specifically target the unique reading profiles of subjects with comorbidities. Children with ASD and comorbid reading problems show a profile of intact decoding abilities, yet low reading comprehension, and accordingly, reading intervention specifically targeting vocabulary skills is shown to be most effective in this population ( 107 , 108 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Reading intervention may also need to specifically target the unique reading profiles of subjects with comorbidities. Children with ASD and comorbid reading problems show a profile of intact decoding abilities, yet low reading comprehension, and accordingly, reading intervention specifically targeting vocabulary skills is shown to be most effective in this population ( 107 , 108 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Studies exploring the relationship between measures of IQ and academic achievement for autistic pupils varied in their findings; in some studies, no difference was found for autistic pupils (Eaves and Ho, 1997), while in others the academic performance of the autistic pupils was found to be lower relative to IQ than for their typically developing peers, with Ashburner et al (2010) finding 54% of autistic pupils underachieving and other studies placing the figure even higher, at up to 90% of autistic pupils (Estes, Rivera, Bryan, Cali and Dawson, 2011). Autistic pupils were also found to have accurate self‐concept in mathematics, but not in reading (McCauley et al, 2018) and lower sentence comprehension than their peers (Davidson and Weismer, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Controlled tasks were used in 18 of the studies, both for independent and dependent variables. Highly structured measurement of behaviour was also reflected, including for example eye‐tracking measurement (Davidson and Weismer, 2017; Higuchi et al, 2017), and pedometers to track movement (Wainscot et al, 2008). Observational methods mainly involved observing classroom or playground behaviours (Locke et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The significant role of age in reading comprehension may reflect developmental shifts across our age span of 8 to 14 years. Age was also a significant predictor of ambiguous sentence comprehension in children with ASD and their TD peers across the same age span (Davidson and Ellis Weismer 2017). However, the separate collection timepoints for the WM and language measures versus the reading measures may also account for the significant effect of age.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited through local schools, community centers, or clinics using flyers and website postings and through a research registry at the Waisman Center (ASD group only) for a larger project examining the relationship of oral language and executive function abilities across monolingual typically developing (TD), bilingual TD, children with specific language impairment, and children with ASD (see Ellis Weismer et al 2017; Gangopadhyay et al 2016; Haebig et al 2015; Kaushanskaya et al 2017 for published studies including some of these participants). Following participation in the larger study, the monolingual TD participants and participants with ASD were recruited for the present study on reading abilities upon additional informed parental consent and child/adolescent assent (see Davidson and Ellis Weismer 2017 for a published study including this similar subset of participants). On average, the time between studies was 8.1 months (SD = 6.49).…”
Section: Methodsmentioning
confidence: 99%